Two mutations in the truncated Rep gene RBR domain delayed the Wheat dwarf virus infection in transgenic barley plants - Pavel Cejnar; Ludmila Ohnoutková; Jan Ripl; Tomáš Vlčko; Jiban Kumar Kundu (Journal of Integrative Agriculture)
Wheat dwarf virus (WDV), an important cereal pathogen, is closely related to Maize streak virus (MSV), a model virus of the Mastrevirus genus. Based on its similarity to known MSV resistance strategies, a truncated part of the WDV replication-associated (RepA) gene (WDVRepA215) and the WDV RepA gene with a mutated retinoblastoma-related protein (RBR) interaction domain (WDVRepA215RBRmut) were cloned into the pIPKb002 expression vector and transformed into immature embryos of spring barley cv. Golden Promise plants through Agrobacterium-mediated transformation. A detailed study of T1-generation plants infected by leafhoppers (Psammotettix alienus) fed on infection sources of variable strength was performed over a 5-week period encompassing the initial stages of virus infection. A DNA WDV TaqMan qPCR assay normalized using the DNA puroindoline-b SYBR Green qPCR assay for samples on a per week basis revealed an approximately 2-week delay in WDVRepA215RBRmut plants to WDVRepA215 plants before significant increases in the WDV viral levels occurred. Both WDVRepA215 and WDVRepA215RBRmut plants showed similar levels of transgenic transcripts over the screened period; however, the transgenic plants also showed increased numbers of infected plants compared to the control plants.